Satisfaction of the external client in the professional academic school of Tourism and Business - Espinoza Requejo, Cinthy Catheryne (2018)
The research aimed to determine the external customer satisfaction on the quality of care in the Academic Professional School of Tourism and Business of the Señor de Sipán University - Pimentel. The population consisted of 235 students of the academic semester 2015-II of the Academic Professional School of Tourism and Business of Señor de Sipán University, technical survey and a questionnaire of 32 items with Liker-type scale was used five criteria measurement to measure customer satisfaction and quality of care. The investigation was not applied mixed with a design ex post facto and ultimately the test of Cronbach's alpha was applied to a pilot test to determine the validity of the content. Was obtained as results for external customer satisfaction was 58% (p = 0.09) and quality of care was 61%. The dimensions studied for customer satisfaction were tangibility (62%), reliability (47%), responsiveness (57%), empathy (62%) and safety (54%); as well as for the quality of care in its dimensions of technical quality (61%) and the functional quality (60%) in the Academic Professional School of Tourism and Business at the University Señor de Sipán - Pimentel. It was concluded that there is correlation between external customer satisfaction and quality of care at a level of 0.866 (p = 0.09).